2016
DOI: 10.1016/j.compchemeng.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry breaking in MILP formulations for Unit Commitment problems

Abstract: Please cite this article as: Ricardo M. Lima, Augusto Q. Novais, Symmetry Breaking in MILP Formulations for Unit Commitment Problems, Computers and Chemical Engineering (2015), http://dx.doi.org/10. 1016/j.compchemeng.2015.11.004 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…In Equations (5) and (6), z h,u,t , u h,u,t and w h,u,t are, respectively, the start-up, shut-down and status decisions of hydropower plant h's generating unit u in time t. Additionally, TU H h and TD H h are, respectively, the minimum uptime and downtime of hydro plant h's units. The set H is the set of hydropower plants and set U h is the set of generating units of plant h. Constraint (7) aims at reducing the symmetry 26 of the hydro problem: unit u + 1 of plant h can only operate if unit u of the same plant is operating in time t. In Equation 7, U gr h,j is the set of generating units in the j group of similar units installed at plant h.…”
Section: The Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…In Equations (5) and (6), z h,u,t , u h,u,t and w h,u,t are, respectively, the start-up, shut-down and status decisions of hydropower plant h's generating unit u in time t. Additionally, TU H h and TD H h are, respectively, the minimum uptime and downtime of hydro plant h's units. The set H is the set of hydropower plants and set U h is the set of generating units of plant h. Constraint (7) aims at reducing the symmetry 26 of the hydro problem: unit u + 1 of plant h can only operate if unit u of the same plant is operating in time t. In Equation 7, U gr h,j is the set of generating units in the j group of similar units installed at plant h.…”
Section: The Problemmentioning
confidence: 99%
“…To account for possible load curtailments or excess of generation, we introduce the slack variables δ + b,t,s and δ − b,t,s , respectively. The nonnegativity requirement for these variables is enforced in Equation (26). The flow f l, t, s is given in Equation 27, where x l is line l's reactance, and θ b f l ð Þ,t,s and θ b t l ð Þ,t,s are line l's from and to buses, respectively.…”
Section: The Problemmentioning
confidence: 99%
“…LR is combined with a genetic algorithm (GA) to obtain satisfactory results for operational cost minimization UC problem in [64]. By implementing MILP, many UC problems involving ESSs have been solved with objective functions such as peak shaving [65], maximizing energy production by reducing curtailment [66], minimization of cost [67][68][69][70][71], minimization of emissions [72], and so on.…”
Section: Overview Of Algorithms For Solving Uc Problemmentioning
confidence: 99%
“…The results demonstrated that their work is superior to the conventional method with the solution optimality and computation efficiency are improved a lot. Lima et al [6] made a comparison between the case with and without symmetry breaking constraints. The results of their study state that symmetry breaking constraints performance well in UC MILP models without having a significant impact on the size of the model.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this paper presents an improved symmetry breaking approach, which is derived from Reference [1] to diminish symmetry in an efficient way. The UC MILP model comes from [7,8] is taken in this paper without considering ramping up and down constraints as these constraints may prevent the utilization of symmetry breaking constraints [6].…”
Section: Introductionmentioning
confidence: 99%